2018
DOI: 10.22434/ifamr2017.0038
|View full text |Cite
|
Sign up to set email alerts
|

The importance of innovation adoption and generation in linking entrepreneurial orientation with product innovation and farm revenues: the case of vegetable farmers in West Java, Indonesia

Abstract: The growth of modern agrifood markets, especially in Indonesia, has stimulated entrepreneurially oriented farmers to seize business opportunities through innovation. This paper aims to investigate in a dynamic agrifood market if entrepreneurial orientation enhances innovation adoption and generation and if both of these actions enhance product innovation and, eventually, farm revenues of vegetable farmers in West Java, Indonesia. The findings demonstrate that entrepreneurial orientation enhances innovation ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 64 publications
4
17
1
2
Order By: Relevance
“…Innovation orientation (IO) has been found as a driver of business productivity and an accelerator of economic growth [68,69]. IO involves transformation of knowledge to create new products, services, and businesses [70]. The significant relationship between business outputs and innovation orientation has been revealed extensively [71,72].…”
Section: Innovation Orientation and Productivity Enhancementmentioning
confidence: 99%
“…Innovation orientation (IO) has been found as a driver of business productivity and an accelerator of economic growth [68,69]. IO involves transformation of knowledge to create new products, services, and businesses [70]. The significant relationship between business outputs and innovation orientation has been revealed extensively [71,72].…”
Section: Innovation Orientation and Productivity Enhancementmentioning
confidence: 99%
“…The first methodological implication involves the measurement of farmers' EO, and specifically risk-taking, in the context of rural Uganda. Relative to the measurements of farmers' EO in other international contexts (Matsuno et al, 2002;Verhees et al, 2011)-including Indonesia (Etriya Etriya et al, 2018), Ivory Coast (Yessoufou, 2017) Third and last, this study reveals the importance of accessing resources (such as labor) and networks relative to farmers' EO. Importantly, we found that farmers' access to networks represents by far the strongest driver of product and market innovation.…”
Section: Methodological Implicationscontrasting
confidence: 53%
“…Given this definition, this study hypothesizes that farmers' entrepreneurial orientation may play an important role in explaining why some farmers may innovate more than others even when participating to the same MSP. Only one recent study suggests that the relationship between farmers' EO and agricultural innovation may be significant (Etriya Etriya, Scholten, Wubben, Kemp, & Omta, 2018), yet it was done in a different geographical context and outside the scope of MSPs. As such, assessing the relationships between farmers' EO and agricultural innovation in the context of one MSP addresses a current knowledge gap in the MSP literature, that is, how an important psychological trait may explain the heterogeneity of the influence s MSPs have on agricultural innovation in different farmers.…”
Section: Farmers' Entrepreneurial Orientationmentioning
confidence: 99%
See 2 more Smart Citations